We are all friends and family here! How jobseekers react to communal job advertisements - Hommelhoff, Sabine; Götz, Davina (Zeitschrift für Arbeits- und Organisationspsychologie, 2023)
Organizations trying to attract talents sometimes promise friendships or family-like workplace relations in their job advertisements. This research examined how jobseekers of different ages react to such promises of communal workplace relationships. In two experiments (N = 292 and N = 343), we found consistent evidence that, compared to conventional exchange-oriented job advertisements, communal job advertisements led jobseekers to assume lower organizational performance standards. However, no differences were apparent in their job-choice intentions. While the jobseekers' age did not moderate these relationships, we found that older employees generally expected higher organizational performance standards. These experiments combine relationship and recruitment research and contribute to our understanding of how people react to the mingling of different relationship norms in the work context. Practically speaking, the findings suggest that the usage of communal job advertisements might not be in the best interest of organizational performance.
CRIS-Team WoS Importer:2022-03-25